A ubiquitous but ineffective intervention: Signs do not increase hand hygiene compliance - David J. Birnbach; Lisa F. Rosen; Maureen Fitzpatrick; Ruth Everett-Thomas; Kristopher L. Arheart (Elsevier, 2017)
Summary: Proper hand hygiene is critical for preventing healthcare-associated infection, but provider compliance remains suboptimal. While signs are commonly used to remind physicians and nurses to perform hand hygiene, the content of these signs is rarely based on specific, validated health behavior theories.This observational study assessed the efficacy of a hand hygiene sign disseminated by the Centers for Disease Control and Prevention in an intensive care unit compared to an optimized evidence-based sign designed by a team of patient safety experts. The optimized sign was developed by four patient safety experts to include known evidence-based components and was subsequently validated by surveying ten physicians and ten nurses using a 10 point Likert scale.Eighty-two physicians and 98 nurses (102 females; 78 males) were observed for hand hygiene (HH) compliance, and the total HH compliance rate was 16%. HH compliance was not significantly different among the signs (Baseline 10% vs. CDC 18% vs. OIS 20%; p = 0.280).The findings of this study suggest that even when the content and design of a hand hygiene reminder sign incorporates evidence-based constructs, healthcare providers comply only a fraction of the time. Keywords: Healthcare-associated infection, Hand hygiene, Public health, Visual cues, Signs